Transitional cell carcinoma of the bladder with parotid metastasis: a case report. (September 2013) - Kitchen, M; Pugh, A; Wharton, Ip; Bhatt, Ri
Transitional cell carcinoma (TCC) of the bladder is the most common urothelial malignancy. Sites of metastatic spread are usually predictable; typically the pelvic and para-aortic lymphatics, followed by extra-vesical tissues, i.e. liver, lung, bone and adrenal glands. There is currently little literature describing metastatic spread to the head and neck region, and none to the authors' knowledge, of spread to the parotid salivary glands. This report describes a rare case of parotid metastasis of bladder TCC in a 75-year-old Caucasian woman.